ANALISIS TINGKAT KEPUASAN WISATAWAN NUSANTARA PADA MASA PANDEMI COVID 19 DI BALI BIRD PARK, GIANYAR - Cokorda Istri Avrilya Shinta Sanjaya; I Nyoman Sudiarta; Putu Agus Wikanatha Sagita (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
There has been a decline in domestic visits due to the Covid-19 pandemic, which has created a crisis in Bali Bird Park as a conservation area. The crisis due to the Covid 19 pandemic makes the attraction of animal conservation must strive to get income, not only the income sought by tourist satisfaction also needs to be considered. This research aims to find out the level of satisfaction of domestic tourists in Bali Bird Park during the Covid 19 pandemic. Referring to service management and Adaptation of New Habits (AKB) adapted to health protocols, the expected results can show the priority of the level of satisfaction of archipelago tourists when visiting in the new normal. This study was conducted at Bali Bird Park using 90 respondents determined based on the concept of Supranto (2011) indicator multiplied by 5, the sample in this study was selected using the purposive sampling method. The data was collected through questionnaires distributed to tourists who had been to Bali Bird Park during the Covid 19 pandemic, then analyzed using Importance Performance Analysis. The results of this study are: 1) The level of satisfaction of archipelago tourists in Bali Bird Park during the Covid 19 pandemic was in the category of less satisfied overall. During the Covid 19 pandemic, health attributes and health protocols were assessed as top priorities by travelers. Priority that takes precedence in improvement is the ability of employees to communicate, and employees provide fast / responsive service. 2) The priority service attributes desired by tourists during the Covid 19 pandemic are the ability of employees to communicate and employee budget in serving. So this research had recommendation to Bali Bird Park the need to educate employees, in order to be able to provide responsive services.